Head and neck sarcoidosis, from wait and see to tumor necrosis factor alpha therapy: A pilot study. Issue 5 (22nd June 2012) - Knopf, Andreas; Lahmer, Tobias; Chaker, Adam; Stark, Thomas; Hofauer, Benedikt; Pickhard, Anja; Thürmel, Klaus; Bas, Murat
Abstract Background To suggest treatment modalities with respect to the specific requirements of head and neck sarcoidosis. Methods Head and neck sarcoidosis was diagnosed in 31 patients. Treatment regimes comprised wait and see, corticosteroid‐pulse, stable‐dose corticosteroids, or adalimumab. Results In all, 21 patients had isolated head and neck sarcoidosis and a further 8 patients showed concomitant pulmonary sarcoidosis. Two patients with pulmonary sarcoidosis developed subsequent head and neck manifestation. Most patients with isolated head and neck sarcoidosis did not receive systemic therapy. None exhibited relapsing disease. Three patients with head and neck manifestation underwent corticosteroid pulse. Complete remission (CR) was detected for all after 5 months. Six patients were treated with stable‐dose corticosteroids. Five of 6 showed CR after 12 months and 1 of 6 patients partial remission (PR) after 24 months. Five of 6 patients exhibited relapses. Two patients underwent adalimumab therapy and showed PR after 65 or CR after 26 months, respectively. Conclusions Most patients with head and neck sarcoidosis did not require systemic therapy. We suggest corticosteroid‐pulse therapy for patients with severe head and neck manifestation. Adalimumab might be potent for nonresponder. © 2012 Wiley Periodicals, Inc. Head Neck, 2013